PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) - Nuriah Nuriah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This study aims to improve social studies learning outcomes in the material of developed countries and developing countries by using the Cooperative Type Group Investigation (GI) learning model. This research began in August to November 2018, which was held in class IX of the first semester of SMP Negeri 1 Julok. The type of research is Class Action Research with two cycles, each cycle consisting of: planning, implementation, observation and reflection. The data collection techniques and tools in this study used descriptive analysis techniques for data in the form of student work documents, and observation sheets. Before the research was conducted the average score of students was only 62.29 with mastery learning from 24 students, only 9 students (37.50%) were complete. In the first cycle student learning outcomes began to increase by 72.29 with mastery learning as many as 16 students (66.67%) were completed. In the second cycle learning outcomes increased sharply to 82.50 with the number of students completing as many as 23 students (95.83%). Based on the achievement of learning outcomes it can be concluded that the use of the Cooperative Type Group Investigation (GI) learning model can improve social studies learning outcomes of material in developed and developing countries in class IX students of the first semester of State Junior High School 1, 2018-2019